First‐principles study of vibrational properties of TiSiO4 clusters. Issue 14 (12th March 2019) - Majid, Abdul; Batool, Amber; Khan, Salah Ud‐Din; Haider, Sajjad
Abstract: First‐principles calculations were performed to investigate the vibrational properties of monomers and dimers of titania, silica, and titania‐silica hybrid clusters. Density functional theory‐based formulism was employed to optimize the geometry at the B3LYP level and calculate the infrared and Raman spectra of the clusters by using the GGA‐PBE exchange‐correlation functional. It was found that the vibrational spectra of Ti2 O4, Si2 O4, and TiSiO4 hybrid clusters provide fingerprint information about structures and structural transitions during the formation of cluster structures. In the case of Si2 O4 the mode at 410 cm −1 exhibited the largest vibration of Si atoms, whereas in the case of Ti2 O4 the mode at 442 cm −1 exhibited the largest vibration of Ti atoms. The hybrid cluster TiSiO4 was structured using two different methods to explore the effects of starting geometry on the structures and vibrational modes of the clusters. The structural properties of the clusters remained unchanged but vibrational modes were found to be different. It is found that Si shows notable vibrations, but the metal atom Ti merely shows any vibration in the case of TiSiO4 hybrid clusters. The low and intermediate frequency modes were stiffened, whereas the three highest frequency modes were softened when the starting geometry of the hybrid clusters was changed from Si2 O4 to Ti2 O4 . Abstract : The study of TiO2 ‐based clusters is an important research area due to their wide range of applications. The vibrational properties studied via first‐principles methods give insights into the structure of the materials. In this study, hybrid TiO2 ‐SiO2 clusters were also prepared by two methods pictorially sketched in the figure. The study of pure and hybrid clusters revealed that, out of 12 modes of vibration, the lower frequency modes associated with symmetric stretching and higher frequency modes are related to the cluster bending modes of vibration.